On Completeness of Fuzzy Normed Spaces - Mohammed, Rana Adnan; A. Ahmed, Buthainah A; F. S., Fadhel (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, a new direction has been presented between the subject of domain theory and fuzzy normed spaces to introduce the so called fuzzy domain normed spaces and proved some results related to this subject concerning the completeness of such spaces.domain